Seeing to Choose: Understanding Parental Visual Preferences in Selecting Early Childhood Equipment - Dinda Robayanti; Ridha Ainnunnisa (Atfaluna: Journal of Islamic Early Childhood Education, 2025)
This study aims to identify parents’ color preferences, sources of visual inspiration, and the roles of family members in decision-making when selecting products for early childhood. Using a quantitative descriptive approach, data were collected through an online survey involving 185 parents. The instrument included a color preference scale, Likert-based attitude statements, and comparative visual image selections. Descriptive statistical analysis was employed to interpret the data. The findings indicate that bright colors remain dominant for products such as toys and clothing, reflecting associations with playfulness and stimulation. In contrast, neutral tones, such as beige and earth colors, are more frequently preferred for educational products and room settings, as they are perceived to promote calmness and visual comfort for children. Direct visual encounters with products and exposure to social media content emerge as the primary sources of visual inspiration. At the same time, mothers are identified as the main decision-makers regarding children’s product selection within the family. These results suggest that parents’ visual choices are shaped not only by functional considerations but also by lifestyle aspirations and aesthetic values believed to support children’s development. Within this context, color functions as a symbolic representation of family identity and parental expectations for children’s everyday environments. This study recommends that designers, manufacturers, and early childhood education practitioners give greater consideration to visual aspects in product development and calls for further research on the developmental implications of visual design in early childhood settings.